CaMKIIδ post-translational modifications increase affinity for calmodulin inside cardiac ventricular myocytes. (December 2021) - Simon, Mitchell; Ko, Christopher Y.; Rebbeck, Robyn T.; Baidar, Sonya; Cornea, Razvan L.; Bers, Donald M.
Abstract: Persistent over-activation of CaMKII (Calcium/Calmodulin-dependent protein Kinase II) in the heart is implicated in arrhythmias, heart failure, pathological remodeling, and other cardiovascular diseases. Several post-translational modifications (PTMs)—including autophosphorylation, oxidation, S -nitrosylation, and O -GlcNAcylation—have been shown to trap CaMKII in an autonomously active state. The molecular mechanisms by which these PTMs regulate calmodulin (CaM) binding to CaMKIIδ—the primary cardiac isoform—has not been well-studied particularly in its native myocyte environment. Typically, CaMKII activates upon Ca-CaM binding during locally elevated [Ca]free and deactivates upon Ca-CaM dissociation when [Ca]free returns to basal levels. To assess the effects of CaMKIIδ PTMs on CaM binding, we developed a novel FRET (Förster resonance energy transfer) approach to directly measure CaM binding to and dissociation from CaMKIIδ in live cardiac myocytes. We demonstrate that autophosphorylation of CaMKIIδ increases affinity for CaM in its native environment and that this increase is dependent on [Ca]free . This leads to a 3-fold slowing of CaM dissociation from CaMKIIδ (time constant slows from 0.5 to 1.5 s) when [Ca]free is reduced with physiological kinetics. Moreover, oxidation further slows CaM dissociation from CaMKIIδ T287D (phosphomimetic) upon rapid [Ca]free chelation and increases FRET between CaM and CaMKIIδ T287A (phosphoresistant). The CaM dissociation kinetics–measured here in myocytes–are similar to the interval between heartbeats, and integrative memory would be expected as a function of heart rate. Furthermore, the PTM-induced slowing of dissociation between beats would greatly promote persistent CaMKIIδ activity in the heart. Together, these findings suggest a significant role of PTM-induced changes in CaMKIIδ affinity for CaM and memory under physiological and pathophysiological processes in the heart. Graphical abstract: Unlabelled Image Highlights: First known report of CaMKIIδ and CaM interaction kinetics in live cardiac myocytes. CaMKIIδ and CaM interactions were measured via novel FLIM-FRET approaches. CaM affinity is increased by CaMKIIδ autophosphorylation in live cardiac myocytes. Autophosphorylation is needed for CaMKIIδ oxidation-mediated CaM affinity increase. Increased CaM affinity may worsen persistent CaMKIIδ activity in cardiac disease.